Douglas Webber, European disintegration? The Politics of Crisis in the European Union - Sánchez Gómez, Manuela (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
Este artícfulo reseña: Douglas Webber, European disintegration? The Politics of Crisis in the European Union. London. Red Globe Press, 2019, 278 pp.